Solubility Enhancement of Simvastatin through Surfactant Addition for Development of Hydrophobic Drug-Loaded Gelatin Hydrogel - Niswati Fathmah Rosyida; Pinandi Sri Pudyani; Akhmad Kharis Nugroho; Ika Dewi Ana; Teguh Ariyanto (Indonesian Journal of Chemistry, 2019)
This study aims to synthesize simvastatin hydrogel as drug delivery system with surfactant addition for improving solubility of simvastatin. Surfactants used in the study were the zwitterionic amino acid of arginine and nonionic surface-active agent of polysorbate 80. The solubility study was conducted by pouring of an excess mass of simvastatin into the solution of a surfactant in a conical flask. The sample was shaken up to 72 h in a mechanical water bath shaker at a varied temperature of 25, 40, and 50 °C. The amount of drug dissolved in solution was analyzed by UV/Visible spectrophotometer at 238 nm. The results showed that the simvastatin solubility is profoundly influenced by the surfactant type, surfactant concentration, and temperature. Polysorbate 80 exhibited as a better surfactant than arginine and an enhancement up to 1400 times, in respect of without any addition of a surfactant, was observed. Based on the solubility study, simvastatin-loaded gelatin hydrogel composite was formulated and the characterization (FTIR and SEM) showed the successful impregnation. The hydrogel microparticles of featured swelling indexes in the range of 2–6 for every patch and presented a sustained release profile.